The Potential Role of Fc-Receptor Functions in the Development of a Universal Influenza Vaccine - Sinthujan Jegaskanda (Vaccines, 2018)
Despite global vaccination efforts, influenza virus continues to cause yearly epidemics and periodic pandemics throughout most of the world. Many of us consider the generation of broader, potent and long-lasting immunity against influenza viruses as critical in curtailing the global health and economic impact that influenza currently plays. To date, classical vaccinology has relied on the generation of neutralizing antibodies as the benchmark to measure vaccine effectiveness. However, recent developments in numerous related fields of biomedical research including, HIV, HSV and DENV have emphasized the importance of Fc-mediate effector functions in pathogenesis and immunity. The concept of Fc effector functions in contributing to protection from illness is not a new concept and has been investigated in the field for over four decades. However, in recent years the application and study of Fc effector functions has become revitalized with new knowledge and technologies to characterize their potential importance in immunity. In this perspective, we describe the current state of the field of Influenza Fc effector functions and discuss its potential utility in universal vaccine design in the future.